Quality Deterioration in Commercial Virgin Coconut Oil Due to Photooxidation and Autooxidation - Ambar Rukmini; Sri Raharjo; Pudji Hastuti; Supriyadi Supriyadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
The objective of this study was to investigate the keeping quality of commercial virgin coconut oil (VCO) and toidentify the probable cause of its quality deterioration. Fourteen brands of commercial VCO and a fresh prepared VCO were used. Sensory evaluation on odor and taste was conducted. Free fatty acid (FFA), moisture, peroxide value (PV), tocopherol, carotenoid, chlorophyll-a, total phenolics content, and fatty acid compounds of VCO were analyzed. In order to observe the effect of photooxidation on the keeping quality, a fresh prepared VCO was packed in a transparent glass bottle and exposed to fluorescent light at 4,000 lux at room temperature for 5 h. PV of the samples were measured at 1 h interval. The results indicated that 10 out of 14 commercial VCO had PV of 1.0 meq/kg or higher and objectionable odor and taste were clearly detected by panelists. The PV of fresh prepared VCO was 0.14 meq/kg oil and only within3 h of light exposure (4,000 lux) its PV reached 1.0 meq/kg oil. Naturally present antioxidants in the VCO were not effective for inhibiting photooxidation, while existing of 0.098 ppm chlorophyll-a effectively sensitized photooxidation reaction. This study confirmed that once the VCO undergoes brief photooxidation, subsequent protection using light barrier packaging material will not effective to inhibit quality deterioration during trading, display, or storage.